2014
DOI: 10.3892/ol.2014.2790
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade myofibroblastic sarcomas of the maxilla

Abstract: Low-grade myofibroblastic sarcoma (LGMS) is a distinct mesenchymal myofibroblastic malignancy. The tumor may occur at a variety of sites, but is particularly associated with the head and neck. Of the two maxillary sarcomas that were analyzed in the present study, one was misdiagnosed as an inflammatory myofibroblastic tumor during pre-operative excision biopsy, and later presented with a different immunophenotype upon recurrence. Representative paraffin blocks from formalin-fixed tissues were selected from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…As presented in Table I, LGMS has been reported to occur in a number of locations in the head and neck region (1,2,4,6,13,1540). Of these, three cases of LGMS in the cheek have reported, including the present case, one case located at the nasolabial fold and one from the buccal mucosa (16,23).…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Table I, LGMS has been reported to occur in a number of locations in the head and neck region (1,2,4,6,13,1540). Of these, three cases of LGMS in the cheek have reported, including the present case, one case located at the nasolabial fold and one from the buccal mucosa (16,23).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused only on low-grade myofibroblastic sarcoma. Low-grade myofibroblastic sarcoma generally affects adult males (average age: 40 years), but cases of all age groups have been reported to date [5][6][7]. This tumor can develop throughout the body, but the most common location is the cervicofacial region.…”
Section: Discussionmentioning
confidence: 99%
“…The limits of the invasion are macroscopically indistinguishable, and radiological examination is needed to detect infiltration and bone damage with respect to the lesion [11]. This tumor is a highly infiltrating and slowly developing tumor with a low metastatic potential and is usually revealed after a long period of indolence [6,12]. In a study (2012) on 38 cases of lowgrade myofibroblastic sarcoma, Yamada et al reported a recurrence rate of approximately 38%, which correlated to the tumor size [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio-immunoprecipitation assay lysate buffer (1 ml) was added into the powder and the supernatant was transferred to a 1.5 ml Eppendorf tube for 30-min lysis on ice. The concentration of HoxB8 protein in the 50 samples embedded in paraffin wax was measured using the immunohistochemical streptavidin-biotin complex method (14). Phosphate-buffered saline was used for the negative control and image of the positive control was from GE Healthcare Life Sciences.…”
Section: Rt-pcrmentioning
confidence: 99%